Incidence of maternal near-miss events in a tertiary care hospital of Gujarat, India - Kansara, Vijay; Vaja, Disha; Desai, Ajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal near miss is said to have occurred when women presented with life threatening complication during pregnancy, child birth and within 42 days after delivery, but survive by chance or good institutional care. For identifying near-miss cases five-factor scoring system was used. In 2009 WHO working group has standardized the criteria for selecting these cases. Because maternal mortality is a rare event, it is important to study maternal near-miss as a complement to evaluate and improve the quality of obstetric care. Thus, the study was conducted with the aim of assessing the incidence and causes of maternal near-miss. Methods: A facility-based cross-sectional study was conducted in the department of obstetrics and gynecology in GMERS medical college and hospital, Sola, Ahmedabad from January 1, 2019 to August 31, 2019. All maternal near-miss cases admitted to the hospital during the study period were recruited. World Health Organization criteria were used to identify maternal near-miss cases. The number of maternal near-miss cases over one year per 1000 live births occurring during the same year was calculated to determine the incidence of maternal near-miss. Underlying and contributing causes of maternal near-miss were documented from each participant’s record. Results: During the period of study, 3235 deliveries were done at the institution while 16 cases of near-miss were identified. The prevalence of near-miss case in this study was 0.5%. Near-miss per 1000 delivery was 5%. Maternal death to near miss ratio was 1:2.67. The leading causes of maternal near miss were hypertensive disorders (62%) and haemorrhage (32%) The morbidity was high in un-booked cases. Conclusions: Maternal near miss is good alternative indicator of health care system. Efforts made toward improvement in the management of life-threatening obstetric complications could reduce the occurrence of maternal near-miss problems that occur during hospitalization.